Anterograde Tracing From the Göttingen Minipig Motor and Prefrontal Cortex Displays a Topographic Subthalamic and Striatal Axonal Termination Pattern Comparable to Previous Findings in Primates - Steinmüller, Johannes Bech; Bjarkam, Carsten Reidies; Orlowski, Dariusz; Sørensen, Jens Christian Hedemann; Glud, Andreas Nørgaard (Frontiers in Neural Circuits, 2021)
Background: Deep brain stimulation (DBS) of the dorsal subthalamic nucleus (STN) is a validated neurosurgical treatment of Parkinson’s Disease (PD). To investigate the mechanism of action, including potential DBS induced neuroplasticity, we have previously used a minipig model of Parkinson’s Disease, although the basal ganglia circuitry was not elucidated in detail. Aim: To describe the cortical projections from the primary motor cortex (M1) to the basal ganglia and confirm the presence of a cortico-striatal pathway and a hyperdirect pathway to the subthalamic nucleus, respectively, which is known to exist in primates. Materials and Methods: 5 female Göttingen minipigs were injected into the primary motor cortex (n=4) and adjacent prefrontal cortex (n=1) with the anterograde neuronal tracer, Biotinylated Dextran Amine (BDA). Four weeks later the animals were sacrificed and the brains cryosectioned into 30 µm thick coronal sections for subsequent microscopic analysis. Results: The hyperdirect axonal connections from the primary motor cortex were seen to terminate in the dorsolateral STN, whereas the axonal projections from the prefrontal cortex terminated medially in the STN. Furthermore, striatal tracing from the motor cortex was especially prominent in the dorsolateral putamen and less so in the dorsolateral caudate nucleus. The prefrontal efferents were concentrated mainly in the caudate nucleus and to a smaller degree in the juxtacapsular dorsal putamen, but they were also found in the nucleus accumbens and ventral prefrontal cortex. Discussion: The organization of the Göttingen minipig basal ganglia circuitry is in accordance with previous descriptions in primates. The existence of a cortico-striatal and hyperdirect basal ganglia pathway in this non-primate, large animal model may accordingly permit further translational studies on STN-DBS induced neuroplasticity of major relevance for future DBS treatments.